Naturally selected honey bee (Apis mellifera) colonies resistant to Varroa destructor do not groom more intensively. Issue 4 (8th August 2017) - Kruitwagen, Astrid; van Langevelde, Frank; van Dooremalen, Coby; Blacquière, Tjeerd
Abstract : The ectoparasitic mite Varroa destructor is an important cause of high colony losses of the honey bee Apis mellifera . In The Netherlands, two resistant A. mellifera populations developed naturally after ceasing varroa control. As a result, mite infestation levels of the colonies of these populations are generally between 5–10%. However, the mechanisms behind mite resistance are still unclear. Since grooming behavior is a typical resistance trait that occurs in A. mellifera, we compared grooming between colonies of these two resistant populations and control colonies that had been treated against varroa twice a year in previous years. Grooming was investigated by measuring mite fall in broodless colonies in the field and in small cages with a fixed number of mites and bees in the lab. Furthermore, grooming was investigated at the individual level by measuring the effectiveness to remove dust by individual bees from the resistant and control colonies. We found that the grooming behavior of resistant colonies was unexpectedly equally or even less effective than that of control colonies. These results were supported by the effectiveness of individual bees to remove dust. Based on our results, we discuss that the trigger for grooming behavior may be density-dependent: grooming may be only beneficial at high mite infestation levels. Other resistance mechanisms than grooming are more likely to explain the varroa resistance of our two populations. Abstract : UF0001